Entrepreneurial Intention among Vocational High School Students in Cirebon: A Need for Achievement Perspective - Kurjono Kurjono; Sulthan Yusuf Abdullah; Aminu Umar; Nurlatifah Nurlatifah (Institute of Multidisciplinary Research and Community Service, 2026)
This study aims to examine the influence of the need for achievement on students' social entrepreneurship intentions by considering the mediating role of perceived desirability and perceived feasibility based on Intention Theory in Shapero's Entrepreneurial Event Model. This study is motivated by the critical importance of developing social entrepreneurship mindsets in the younger generation, particularly among vocational high school (SMK) students, as an effort to create competent individuals who are not only oriented toward economic gain but also deeply concerned with solving complex social problems in society. The research method used is an explanatory survey design utilizing a quantitative approach. The research sample consisted of 195 vocational high school students in Cirebon, selected from the total population using a purposive sampling technique. Data collection was carried out by distributing structured questionnaires compiled comprehensively based on the specific indicators of each research variable. Furthermore, the collected data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS software version 3. The results showed that the need for achievement has a positive and significant direct effect on students' social entrepreneurship intentions. This means that the higher students' inner drive for achievement, the higher their tendency to intend to become social entrepreneurs. Furthermore, perceived desirability and perceived feasibility were statistically proven to partially mediate the relationship between need for achievement and social entrepreneurial intention. Based on these empirical findings, this study concludes and recommends the urgent need for entrepreneurship curriculum renewal by integrating core social entrepreneurship values, experiential learning, structured internship programs, and strengthening business incubator activities within vocational schools. Keywords: Entrepreneurial intention, Need for achievement, Perceived desirability, Perceived feasibility, Vocational high school students.